2015
DOI: 10.1002/bjs.9758
|View full text |Cite
|
Sign up to set email alerts
|

International validation of a risk score for complications and reinterventions after endovascular aneurysm repair

Abstract: This study has provided international validation of a morphological risk score that predicts mid-term reinterventions and endograft complications. The results may enable risk-stratified surveillance after EVAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
(39 reference statements)
3
12
0
Order By: Relevance
“…20 A recent validation of their original study revealed a significant difference in freedom from endograft complications at 3 years. 21 Our study supports the notion that patients are at increased or decreased risk due to their individual anatomy. The low rates of implant-related and systemic complications in the lowscore ASG group suggest that these patients may not require a 6-month or even a 1-year follow-up.…”
Section: Discussionsupporting
confidence: 87%
“…20 A recent validation of their original study revealed a significant difference in freedom from endograft complications at 3 years. 21 Our study supports the notion that patients are at increased or decreased risk due to their individual anatomy. The low rates of implant-related and systemic complications in the lowscore ASG group suggest that these patients may not require a 6-month or even a 1-year follow-up.…”
Section: Discussionsupporting
confidence: 87%
“…8, Five secondary studies described external validation of risk scores for reintervention or aortic complications. 43,[46][47][48][49] The 29 primary studies reported 39 898 patients, with study midpoints ranging from 1998 to 2011. Predictors of aortic complications and reintervention were identified from preoperative, intraoperative, and postoperative EVAR data (Table 1).…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…Five publications reporting data from the ENGAGE registry were identified in the literature [93][94][95][96][97] ( Table 10). The study by Tang et al, 93 which compared the 12 outcomes after repair of AAA with bifurcated versus aorto-uni-iliac configuration of the Endurant stent-graft, used data collected in the ENGAGE registry from March 2009 to August 2010.…”
Section: The Endurant Stent Graft Natural Selection Global Postmarketmentioning
confidence: 99%
“…The study by Karthikesalingam et al 95 used data from the ENGAGE registry on reintervention and engraft complications at 3 years to predict whether patients would be at a low risk or a high risk of complications after EVAR based on the international validated St George's Vascular Institute score. 95 Overall, there were Stokmans 2012 94 Tang (2013) 93Karthikesalingam 2015; 95 and Bastos Goncalves (2015) 97 Faure 2015 94 Tang (2013) 93Karthikesalingam (2015); 95 and Bastos Goncalves (2015) 97 Faure (2015) 96All-cause mortality, n (%) 16 1.342 8.414 1.328 8.6Procedure-related mortality (up to 30 days)…”
Section: The Endurant Stent Graft Natural Selection Global Postmarketmentioning
confidence: 99%
See 1 more Smart Citation